Analisis Strategi Menulis Terbimbing Dalam Keterampilan Menulis Siswa Kelas IV SDN 05 Muara Ilai - Basilius Ronaldino; Yuli Budhiarti (Lembaga Teewan Journal Solutions, 2026)
This study aims to describe the implementation of guided writing strategies in improving the writing skills of fourth-grade students at SDN 05 Muara Ilai. The background of this study is the low writing ability of several students, especially in forming letters, organizing ideas, maintaining concentration, and producing readable writing. This research used a descriptive qualitative approach with an exploratory case study design. The subjects were the fourth-grade teacher and students, focusing on six students who experienced writing difficulties. Data were collected through observation, interviews, and documentation. The findings show that students’ difficulties were influenced by internal factors, such as weak fine motor skills, limited letter manipulation ability, low concentration, and lack of confidence, as well as external factors, including limited learning support and less varied writing practice. The implementation of guided writing strategies through planning, drafting, revising, and direct teacher guidance helped students improve pencil control, letter formation, neatness, focus, and confidence. Therefore, guided writing strategies are effective in supporting elementary students’ writing skills.